The (Alleged) Environmental and Social Benefits of Dynamic Pricing - Matthew Harding; Kyle Kettler; Carlos Lamarche; Lala Ma (Institute of Labor Economics (IZA), 2021)
This paper provides a cautionary tale about claiming environmental costs and benefits when justifying the use of public funds. Using the example of a dynamic pricing policy, we show that the resulting impact on short-term operating costs and emissions is at best ambiguous. Moreover, it is hard to quantify even in ideal scenarios where data is plentiful and the behavioral response can be estimated precisely using a randomized control trial of customers of an electric utility. While dynamic pricing has been touted as a means to control generation costs and pollution, price-induced reallocation of electricity consumption within a day may actually increase net emissions depending on the source-generation mix of a region.
Keywords: D12; L11; L94; Q53; Q58; 330; dynamic pricing; randomized experiment; load shifting; air pollution